ANTIBIOTIC RESISTANCE PROFILES OF CARIOGENIC BACTERIA ISOLATED FROM THE ORAL CAVITIES OF UZBEK POPULATION: https://doi.org/10.5281/zenodo.15240158 - Gulomov, J. I.; Normatov , A. M.; Abdunabiev , A. M.; Urmonalieva , Sh. U.; Abduvokhidova , Y.O.; Reyimbergenova , Z. A.; Oltiboeva , Kh. A; Dalimova, D. A; Sohibnazarova , Kh. A (International scientific and practical conference, 2025)
Based on information from the World Health Organization, almost 2 billion adults have permanent tooth decay, while 514 million children have primary tooth decay. Although several studies on caries in Uzbekistan, there is still a lack of evidence on the involvement of cariogenic microorganisms. This study isolated cariogenic bacteria from a middle-aged Uzbek population with caries and determined their antibiotic resistance profile.